1998
DOI: 10.1038/bjc.1998.84
|View full text |Cite
|
Sign up to set email alerts
|

Frequent and heterogenous expression of cyclin-dependent kinase inhibitor WAF1/p21 protein and mRNA in urothelial carcinoma

Abstract: No mutations were observed in the WAF1/p21 gene in these tumours, but two were heterozygous for the codon 31 polymorphism. These data indicate that p21 is frequently expressed in superficial, well differentiated urothelial carcinomas, but less often in muscle-invasive urothelial carcinomas, irrespective of their p53 status. The expression of p21 and its prevalence in low-stage tumours may reflect residual growth-regulatory influences potentially impeding but not necessarily inhibiting tumour development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0
2

Year Published

1999
1999
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 30 publications
4
27
0
2
Order By: Relevance
“…In our study, p21 staining did not correlate with tumour grade, which is in accordance with several recent observations in different neoplasms Slebos et al, 1996;Byrne et al, 1997). Overexpression of p21 has also been observed in low-grade (IÐII) urothelial tumours (Clasen et al, 1998). In addition, Doglioni et al (1996), Wang et al (1997) and Yasui et al (1997) described higher p21 expression in stages 0Ð2 colon carcinomas than in stages 3 and 4 carcinomas.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…In our study, p21 staining did not correlate with tumour grade, which is in accordance with several recent observations in different neoplasms Slebos et al, 1996;Byrne et al, 1997). Overexpression of p21 has also been observed in low-grade (IÐII) urothelial tumours (Clasen et al, 1998). In addition, Doglioni et al (1996), Wang et al (1997) and Yasui et al (1997) described higher p21 expression in stages 0Ð2 colon carcinomas than in stages 3 and 4 carcinomas.…”
Section: Discussionsupporting
confidence: 80%
“…In addition, Doglioni et al (1996), Wang et al (1997) and Yasui et al (1997) described higher p21 expression in stages 0Ð2 colon carcinomas than in stages 3 and 4 carcinomas. There is also evidence supporting the hypothesis that p21 may exert its tumour suppressive effects in the early stages of tumour development (Ogawa et al, 1997;Clasen et al, 1998) to which the present study gives further strengthening. However, some cancer studies have not revealed any association between tumour stage and p21 expression (Slebos et al, 1996;Byrne et al, 1997;Bennet et al, 1998).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Quantitative analysis of mRNA levels was performed essentially as described (Clasen et al, 1998;Oya et al, 1998). Primer sequences and amplification conditions are listed in Table 2.…”
Section: Reverse Transcription and Pcrmentioning
confidence: 99%